How Should We Think About Employers' Associations? - Alex Bryson; Paul Willman (Institute of Labor Economics (IZA), 2022)
We maintain that employer associations are a specific form of employer collusion that is overt, formal and labour market focused which encompasses but is by no means confined to collective bargaining. We consider the conditions under which this form of collusion might emerge, and how it might develop. Since the context is the decline of employers' associations in collective bargaining, we look at how collective bargaining involvement (and its disappearance) might relate to the growth or decline of other forms of collusion in areas such as product and financial markets, and political influence. Our central contention is that employers' associations continue to perform an important role in helping employers set the terms of trade, albeit one that has adapted to the demise of sectoral bargaining.
Keywords: J50; J52; 330; employers' associations; collusion; collective bargaining